The effectiveness of psychological skills training and behavioral interventions in sport using single-case designs: A meta regression analysis of the peer-reviewed studies - Barker, J. B.; Slater, M. J.; Pugh, G.; Mellalieu, S. D.; McCarthy, P. J.; Jones, M. V.; Moran, A. (Psychology of Sport and Exercise, 2021)
Highlights • Shooting performance deteriorates over time.